1974
DOI: 10.1002/jss.400020211
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of ribosome assembly

Abstract: The assembly of E. coli ribosomes has been studied through the analysis of a new group of ribosome maturation mutants. These mutants, all blocked in a late stage in the maturation of 50s ribosomes, map at four different sites on the chromosome. These sites are distant from the known ribosomal protein sites a t the str-aro E region of the chromosome. The ribosome precursor particles of the mutants contain precursor-type 2 3 s RNA (p23 RNA) and 5s RNA. 4 3 s particles of one of the mutants contain all but one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…DISCUSSION We previously reported (1) that various methods of cell disruption and/or the use of DOC can alter the physical properties of ribosomal precursor subunits. The data presented in this study indicated that another detergent, LOC, which has been used by Bryant and Sypherd in studies of ribosome assembly (3,19), also alters the sedimentation properties of ribosomal precursor subunits as well as mature 30S subunits ( Fig. 2A).…”
Section: Effects Of Detergents On Ribosomal Precursorsmentioning
confidence: 60%
“…DISCUSSION We previously reported (1) that various methods of cell disruption and/or the use of DOC can alter the physical properties of ribosomal precursor subunits. The data presented in this study indicated that another detergent, LOC, which has been used by Bryant and Sypherd in studies of ribosome assembly (3,19), also alters the sedimentation properties of ribosomal precursor subunits as well as mature 30S subunits ( Fig. 2A).…”
Section: Effects Of Detergents On Ribosomal Precursorsmentioning
confidence: 60%